Neurological Consequences of COVID-19: A Literature Review of Pathophysiology, Clinical Manifestations, and Therapeutic Strategies - Łobaza, Paulina; Kudła, Martyna; Zając, Gabriela; Antkiewicz, Mikołaj; Arczyńska, Aleksandra; Kociuba, Julia; Kołkowicz, Dorota; Kruczek, Zuzanna; Krawczyk, Agata; Pawełczak, Natalia (Quality in Sport, 2025)
The COVID-19 pandemic, caused by SARS-CoV-2, has become a major global health crisis with widespread effects on healthcare, society, and economies. Initially seen as a respiratory illness, it is now recognized as a multisystem disease, with growing evidence of its impact on the nervous system. Neurological complications - such as cognitive impairment ("brain fog"), strokes, Guillain-Barré syndrome, and mood disorders - have been reported in both severe and mild COVID-19 cases, highlighting the unpredictable nature of post-COVID sequelae. These symptoms can persist long after the acute phase of infection. The mechanisms behind these effects are complex and not yet fully understood. They include direct viral invasion of the central nervous system, immune dysregulation (e.g., cytokine storm, autoimmunity), and blood–brain barrier disruption, all of which may lead to neuroinflammation and neurodegeneration. The long-term neurological consequences pose significant clinical and societal challenges, requiring multidisciplinary care and tailored rehabilitation strategies. This review summarizes current knowledge on the neurological manifestations of COVID-19, underlying mechanisms, and therapeutic approaches, aiming to inform evidence-based post-COVID care.